Experimental investigation of electrode shape configuration in sustainable electric discharge machining process. Issue 1 (February 2021) - Murugesh, S; Manikandan, N; Subramaniyan, M; Chockalingam, S; Surendar, G
Abstract: Electric Discharge Machining (EDM) is also known as spark erosion process which is used to machine hard material and complex shape profile. In EDM process, dielectric fluid plays an important role for material removal as well as generates environmental and health related issues. In this work, an experimental effort is made to study the different categories of dielectric by varying shapes of electrodes during machining of die steel. In this work, an attempt of canola oil and jatropha oils used as dielectric fluid and the machining performance are analyzed with kerosene as dielectric fluid. Material Removal Rate (MRR), Tool Wear Rate (TWR) and Surface Roughness (SR) are selected as performance measures. The result observed that higher MRR with canola oil as dielectric compared to commercial dielectric fluid due to its good dielectric properties. Also, it is observed that higher TWR and SR which is required further investigation. Each shape of electrodes and their machining performance are compared with different dielectric fluids and the results indicated that canola oil provides good performance when compared with jatropha and kerosene. This natural and biodegradable dielectric fluid can be replaced for hydrocarbon oil based dielectric fluid.